Redefining Archaeological Research: Digital Tools, Challenges, and Integration in Advancing Methods - Stella Sylaiou; Zoi-Eirini Tsifodimou; Konstantinos Evangelidis; Aikaterini Stamou; Ioannis Tavantzis; Alexandros Skondras; Efstratios Stylianidis (Applied Sciences, 2025)
This paper explores the diverse array of digital tools utilized for data acquisition in archaeology. This abstract outlines the various categories of digital tools commonly employed, including geographic information systems (GISs), global positioning systems (GPSs), remote sensing technologies, 3D scanning and photogrammetry, drones and aerial photography, as well as mobile applications and digital recording systems. Each category is elucidated with examples of their application in archaeological research, emphasizing their roles in site mapping, spatial data collection, artefact documentation, and landscape analysis. Furthermore, it discusses the advancements, challenges, and best practices associated with the integration of digital tools into archaeological fieldwork. It also highlights the potential for future developments in digital technologies to enhance data acquisition capabilities further, ultimately contributing to a deeper understanding of human history and cultural heritage.